Balancing wildlife protection and wildfire threat mitigation using a network optimization approach - Yemshanov, Denys; Dawe, Denyse A.; Bakalarczyk, Amanda; Liu, Ning; Boulanger, Yan; Boucher, Jonathan; Beauchemin, Alexandre; Arseneault, Dominique; Leblond, Mathieu; Parisien, Marc-André (Frontiers in Forests and Global Change, 2023)
In boreal forests of North America, land managers often carry out preventive treatments of forest fuel for the protection of human infrastructure from wildfires. However, these treatments may negatively affect other ecosystem services, such as the capacity to sustain wildlife populations. Here, we examine the efficacy of a strategy aimed at preserving a critical movement corridor for boreal woodland caribou (Rangifer tarandus caribou) in northern Québec, Canada, by raising high-voltage powerline conductors above the forest canopy. To assess the interplay between the caribou protection objectives and a reduction of powerline's exposure to wildfires, we developed an optimization model that combines the objectives of protecting the powerline from wildfires via fuel treatments and maintaining a suitable movement corridor for caribou. The model combines a Critical Node Detection (CND) problem with a habitat connectivity problem that allocates a minimum-resistance fixed-width habitat corridor between isolated wildlife refuges. Our results identify the best locations to perform fire fuel treatments to lessen the threat of fire damages to human infrastructure while maintaining a connectivity corridor for caribou in present and future climate scenarios. The selected fuel treatment locations aimed to mitigate wildfire exposure to a powerline. In smallbudget solutions, the exposure of powerline infrastructure to wildfires was reduced by 36-39% in current climate conditions and by 20-31% in future climate, compared to no-treatment scenarios. Despite the detrimental effects of wildfire to both the industrial asset and caribou habitat, the approach provides strategies that help achieve a compromise between these two values. Such knowledge is timely to help mitigate the negative impacts of climate change on human livelihoods and natural ecosystems.